M8 The effect of distance from the hospital, public transport availabity and socioeconomic deprivation on non-attendance at a difficult asthma clinic. (14th November 2013) - Mayer, J; Abraham, P; Burhan, H; McDonough, BJ; Mault, S
Abstract : Introduction: Regular clinic review is an important factor in reducing morbidity in asthma 1 . In a specialist difficult asthma clinic at our large city centre teaching hospital seeing more than 100 new primary and secondary care referrals per year, 'did not attend' (DNA) rates were 9% higher than in a general respiratory clinic led by the same consultant. A previous study has demonstrated an association between socioeconomic deprivation and non-attendance 2 . We hypothesised distance from the clinic, long public transport journeys and socioeconomic deprivation were related to an increased number of missed appointments. Methods: Data were collected between April 2011 and March 2012 inclusive. Patient criteria included those with a Liverpool postcode who had missed one or more of their appointments. Patients were grouped into categories according to number of DNAs. Distance from hospital; availability and time taken by public transport and socioeconomic status of postcode were reviewed. These were calculated using Google maps; local public travel information services and the Indices of Deprivation 2010 dataset 3 . Results: Eighty-nine patients with Liverpool postcodes were included in the study. Number of DNAs ranged from 1 to 6. Data according to patient group by number of DNAs is displayed below. Only two patients had missed 5 and 6 appointments therefore these groups were excluded from analysis. There was no statistical difference between distance from hospital, time to get to hospital by public transport or socioeconomic status on the number of missed appointments. See Table 1 . Discussion: Reasons for missing clinic appointments are multifactorial and, in our cohort, there was no association found between distance from the hospital, time taken by public transport to reach the hospital or economic deprivation. Assumptions of low socioeconomic status relating to poor clinic attendance are often made by clinicians however there is no evidence to suggest this is valid in our patient group. Reducing DNA's remains an important area of investigation and a key objective of NHS Institution of Innovation and improvement. References: Gibson, PG, Powel H, Coughlin J, et al . Self management education and regular practitioner review for adults with asthma Cochrane Database Syst Rev 2003;(1):CD00117 Hamilton, W., Round, A. & Sharp, D. Patient hospital and general practitioner characteristics associated with nonattendance: a cohort study. British Journal of General Practice . 2002; (314) 317–319. English Indices of Deprivation 2010, Department for Communities and Local governments March 2011, Available from www.gov.uk/governemtn/publications/english-indices-of-deprivation-2012